The Financial Crisis and Policy Responses in Europe (2007–2018). Issue 4 (December 2018) - Mongelli, Francesco; Camba-Mendez, Gonzalo
Abstract In Europe, the financial crisis has gone through several phases of varying complexity before abating in mid-2014. It started with the Financial Turmoil in August 2007, followed by the Global Financial Crisis in September 2008, and the Great Recession in 2009–2010. These events exacerbated imbalances that had been building-up in the euro area. Then, in early 2010 the Sovereign Debt Crisis of the euro area was triggered by unsustainable finances in some countries and overstretched banks. The euro area was then confronted with financial fragmentation, impaired monetary policy transmission, and threats to financial stability. The acute phase of the euro area crisis was followed by weak growth, a second recession, and thereafter a protracted period of disinflation. As the crisis mutated, monetary policy had to respond to ever new challenges. The policy toolkit of the ECB has thus expanded. This paper explains the events as they unfolded against the backdrop of a changing institutional framework, and governance reforms. There is no encompassing study of such an exceptional period. Our paper is the first to bring together the various policy strands. Policy responses are working and have supported a steady recovery of the economy since mid-2014 and changes in its governance.